Exploring Teachers’ Motivational Strategies: Validation and Application of the Teachers’ Student Motivation Scale (TSMS) - Nurdin; Misbahillah, Al Khansa Nova (Master Program in Indonesian Language Education and The Institute for Research and Community Service STKIP PGRI Bandar Lampung, 2025)
This study investigates the motivational strategies employed by teachers through the application of the Teachers’ Student Motivation Scale (TSMS), a psychometrically validated instrument designed to assess teachers’ approaches to student motivation. The TSMS comprises 32 scenario-based items categorized into four sub-dimensions: high-level control, moderate-level control, moderate-level autonomy support, and high-level autonomy support. Utilizing a 5-point Likert scale, the scale captures the frequency and appropriateness of teachers’ motivational behaviors. The study evaluates the reliability and validity of the TSMS, reporting satisfactory internal consistency (Cronbach’s alpha ranging from 0.75 to 0.78 across sub-dimensions) and significant correlations with the Student Locus of Control Scale, indicating meaningful relationships between motivational strategies and students’ locus of control. Data analysis, including independent samples t-tests, explores variations in motivational strategies by teacher gender. Findings highlight the role of control and autonomy-supportive strategies in fostering student motivation, with implications for teacher training and educational practice. This research contributes to the understanding of motivational aspects in educational settings and offers an appropriate tool for future studies.